Strategy Directions for the Potential Development of Robusta Coffee Based on Social Forestry with Value Chain and Added Value Approaches - Yekti A, R. P.; Anggraeni, O. J; CNAWP, R. Perlambang; Djamali, R. A.; Putra, D. E. (Budapest International Research and Critics University, 2022)
LMDH “Rengganis” Pakis Village, Panti Subdistrict, Jember Regency is one of the social forestry programs that involves forest village communities to use it for productive activities and to improve the economy of rural communities around the forest. However, along the way, it faces many obstacles, including the lack of knowledge of farmers, the facilities for developing agro-industry and cooperative institutions at the village level are still limited. The purpose of this study is to design a strategy for developing the Value Chain of coffee products and Added Value of coffee products, as well as to identify opportunities to increase the economic value of coffee products. The method used is descriptive exploratory by determining the area purposively. The analysis technique used is Value chain analysis (VCA) and added value analysis (AVA). The method of collecting data is using a questionnaire through in-depth interviews. The data used consists of primary data and secondary data. Conclusions: (a) Based on the value chain analysis where the main and supporting activities to build the value chain are carried out entirely in the LMDH